2015
DOI: 10.5505/agri.2015.09609
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Epidural Analgesia with Total Intravenous Anesthesia on Risky Patients Underwent Major Abdominal Surgery

Abstract: SummaryObjectives: The aim of this study is to investigate the effects of combined epidural analgesia with total intravenous anaesthesia and only total intravenous anaesthesia on the different clinical parameters. Methods: Sixty high risk patients undergoing a major abdominal surgical procedure were included in this prospective, double blind, randomized study. Induction of anaesthesia was performed with IV remifentanil 0.5µg/kg and propofol titrated to achieve bispectral index score between 40 and 50. after in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…The difference may be due to the combination of epidural and GA in the current study, while in Gonzalez's study, patients who had undergone CEGA, were excluded. In agreement with current findings, CEGA was associated with a shorter time to extubation and PACU stay compared to GA alone after radical prostatectomy, total hysterectomy, and various abdominal procedures (Akarsu Ayazoğlu et al, 2015, Calimli et al, 2012, Tikuisis et al, 2009. Epidural analgesia, after colorectal surgery, could not shorten hospital stay or reduce incidences of PONV or urine retention compared to using patient-controlled analgesia (PCA) with morphine (Cox et al, 2023).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The difference may be due to the combination of epidural and GA in the current study, while in Gonzalez's study, patients who had undergone CEGA, were excluded. In agreement with current findings, CEGA was associated with a shorter time to extubation and PACU stay compared to GA alone after radical prostatectomy, total hysterectomy, and various abdominal procedures (Akarsu Ayazoğlu et al, 2015, Calimli et al, 2012, Tikuisis et al, 2009. Epidural analgesia, after colorectal surgery, could not shorten hospital stay or reduce incidences of PONV or urine retention compared to using patient-controlled analgesia (PCA) with morphine (Cox et al, 2023).…”
Section: Discussionsupporting
confidence: 85%
“…CEGA protocols, including either single shot of bupivacaine/ fentanyl or continuous epidural infusion of ropivacaine/ fentanyl also provided better analgesia, earlier mobility, and more patient satisfaction after spine surgeries (Ezhevskaya et al, 2013, Khajavi et al, 2013. Similar results for CEGA approaches were recorded after various abdominal procedures (Akarsu Ayazoğlu et al, 2015). The reduction of intraoperative analgesic and anesthetic requirements in CEGA with TET group of patients in the current study can be attributed to the combination of epidural/GA approach (Calimli et al, 2012) Suppression of persistent cough in CEGA with TET group was demonstrated in 17/20 patients.…”
Section: Discussionmentioning
confidence: 52%
“…At the end of surgery, due to reducing the amount of general anesthesia and relying on epidural anesthesia to complete the final abdominal closure, suture skin, the postoperative pain was alleviated; extubation time was brought forward, and the recovery time was accelerated. Study of Akarsu Ayazoğlu et al (30) also showed that general anesthesia combined with epidural block could make hemodynamics more stable and recovery time shorter. In the study of Nishikawa et al (31), it was once again demonstrated that sevoflurane might be superior to propofol for general anesthesia and epidural analgesia in elderly patients undergoing long-term laparoscopic surgery, with less impact on patients' mental function.…”
Section: Discussionmentioning
confidence: 97%